Climate change and social networks: the use of Instagram and TikTok among secondary-school students in relation with sustainability - REy, Laia Palos; Diez Bosch, Miriam; Israel Turim, Veronica (Comunicação Mídia e Consumo, 2024)
Climate change has been identified as the greatest challenge facing humanity. In this research we sought to find out the extent to which teenagers use social media to stay informed about the climate emergency and sustainability. We studied the case of 98 teenagers, examining what types of content they view on Instagram and Tik Tok, and which accounts they follow. The main results of this research indicate that these teenagers do not use the analysed platforms to consume content on climate emergency and sustainability, highlighting the need for further educational intervention as a way to promote interest in these issues.